Fatores associados à obesidade em mulheres de três capitais da Região Norte: Vigitel 2023 - (:unkn) unknown (EEM - Escola de Enfermagem de Manaus, 2025)
Introduction: Obesity is a chronic, multifactorial condition expanding globally, with increasing prevalence in Brazil, especially among women in the North Region. Objective: To estimate the factors associated with obesity among adult women in three capitals of the North Region using VIGITEL 2023. Method: Cross-sectional study with secondary data from the Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey, covering Manaus, BoaVista, and Belém. Descriptive analyses and logistic regression (p≤0.05) were performed. Results: A total of 1,506 women were included, of whom 27.8% were obese. There was a positive association with older age (median 42 years) and frequent consumption of fruit juice (OR = 1.57; p=0.016) and an inverse association with regular physical activity (OR = 0.58; p=0.002). Low consumption of beans and vegetables and a higher prevalence of sedentary lifestyle were observed among obese women. Conclusion: Obesity in the studied capitals is related to behavioral and sociodemographic factors, reinforcing the need for intersectoral policies to promote healthy eating and physical activity, considering regional specificities. Limitations include the use of self-reported data and the restriction to urban areas with telephone access.
Keywords: Obesidade; Epidemiologia; Doenças Não-Transmissíveis; CIENCIAS DA SAUDE: ENFERMAGEM